2020
DOI: 10.3390/pr8101252
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Characterization of Cohesive and Non-Cohesive ‘Sediments’ under Different Consolidation States Using 3D DEM Triaxial Experiments

Abstract: The Discrete Element Method has been widely used to simulate geo-materials due to time and scale limitations met in the field and laboratories. While cohesionless geo-materials were the focus of many previous studies, the deformation of cohesive geo-materials in 3D remained poorly characterized. Here, we aimed to generate a range of numerical ‘sediments’, assess their mechanical response to stress and compare their response with laboratory tests, focusing on differences between the micro- and macro-material pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Typically, grains did not have a significant, cohesive force to create surface tension between two types of granular materials (McLaren et al, 2019). It was also reported that for loose sand, which was comparable to dry agricultural grains, the cohesion force should be neglected (Elyashiv et al, 2020).…”
Section: Measurement Of φ (Internal Friction Angle)mentioning
confidence: 99%
“…Typically, grains did not have a significant, cohesive force to create surface tension between two types of granular materials (McLaren et al, 2019). It was also reported that for loose sand, which was comparable to dry agricultural grains, the cohesion force should be neglected (Elyashiv et al, 2020).…”
Section: Measurement Of φ (Internal Friction Angle)mentioning
confidence: 99%
“…The sample of 16,326 balls is shown in Figure 7 a with a size of 2.4 m × 4.8 m (diameter × height). We adopted the contact bond model for soil, which can truly reflect the mechanical properties of clay materials [ 31 , 32 ]. In PFC3D, the idea of obtaining soil’s micro-parameters is as shown in Figure 7 b.…”
Section: Tensile Test and Calibrationmentioning
confidence: 99%